Islam Wasatiyya in the View of Majelis Ulama Indonesia - Juhri, Muhammad Alan; Assegaf, Abdillah; Fauzi, Darma Ami (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2023)
This article examines wasatiyya through the eyes of the Indonesian Ulema Council (MUI). In terms of current religiosity in Indonesian society, most people are polarized into two extreme patterns, namely the extreme right and the extreme left. The role of the Indonesian Ulema Council (MUI) is demonstrated by demonstrating the concept of Islamic wasatiyya taught by the Prophet Muhammad SAW. The emergence of radicalism and liberalism was undoubtedly influenced by several factors, including religious exaggeration or, conversely, taking religious matters lightly. This article specifically seeks to answer two questions. First and foremost, how did the MUI come to be? Second, how does the MUI view the concept of wasatiyya da'wah? Third, what is the role of the Indonesian Ulema Council's (MUI) fatwa for the Indonesian people? As a result, we can see that the MUI, a semi-official institution in Indonesia, plays an important role in religious matters for Indonesian society, including preventing the emergence of extreme right and extreme left views. Until we believe MUI has carried out a religious moderation movement, also known as Wasatiyya al-Islam. Keywords: MUI, Preaching, Radical, Wasatiyya.